Convergent patterns of adaptive radiation between island and mainland Anolis lizards. (2nd June 2021) - Huie, Jonathan M; Prates, Ivan; Bell, Rayna C; de Queiroz, Kevin
Abstract: Uncovering convergent and divergent patterns of diversification is a major goal of evolutionary biology. On four Greater Antillean islands, Anolis lizards have convergently evolved sets of species with similar ecologies and morphologies (ecomorphs). However, it is unclear whether closely related anoles from Central and South America exhibit similar patterns of diversification. We generated an extensive morphological data set to test whether mainland Draconura -clade anoles are assignable to the Caribbean ecomorphs. Based on a new classification framework that accounts for different degrees of morphological support, we found morphological evidence for mainland representatives of all six Caribbean ecomorphs and evidence that many ecomorphs have also evolved repeatedly on the mainland. We also found strong evidence that ground-dwelling anoles from both the Caribbean and the mainland constitute a new and distinct ecomorph class. Beyond the ecomorph concept, we show that the island and mainland anole faunas exhibit exceptional morphological convergence, suggesting that they are more similar than previously understood. However, the island and mainland radiations are not identical, indicating that regional differences and historical contingencies can lead to replicate yet variable radiations. More broadly, our findings suggest that replicated radiations occur beyond island settings more often than previously recognized.